EFFECT OF HEALTH EDUCATION USING VIDEO AND BROCHURE ON MATERNAL HEALTH LITERACY - Indah Prawesti; Fitri Haryanti; Lely Lusmilasari (Belitung Raya Foundation, Indonesia, 2018)
Background: Fever is manifestation of acute disease on children and contributes to incidence of severe malnutrition and morbidity and the most common reason for parents to deliver children on hospital. Currently, parents still lack knowledge of determination and proper management of fever although intervention of health education has been widely practiced. One obstacle to widespread success of educational intervention is inadequacy of health literacy. Utilization of media with simple and completed information with picture can be developed in communities with low levels of health literacy. Objective: To understanding the effect of health education using video and brochure on maternal health literacy in the working area of Saptosari Public Health Center, Gunungkidul Yogyakarta, Indonesia. Methods: This was a quasi-experimental study with pretest and posttest nonequivalent control group design conducted on 15 – 27 May 2017. The questionnaire used was HLS-Asia Q which had been modified. Health education intervention was done using a five minute-duration video about fever management in children preceded by discussion about the content of the video. Cluster sampling technique was applied with mothers who have under five children as the respondent involving 45 respondents for intervention group and 42 respondents in control group. Data analysis used independent sample t-test. Results: There was an increase in average maternal health literacy provided with video and brochure media compared to the maternal health literacy given with standard treatment. Intervention group mean difference value was 6.6444 ± 9.6086 and value of difference of control group mean equals to -2.4762 ± 12.0674 (p value <0.001). Conclusion: Health education intervention using video has a higher impact in the development of maternal health literacy compared with the standard intervention using brochure.